Pareto efficiency of the pay-as-you-go pension system in a three-period-OLG model - Matthias Wrede (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 1998)
The paper considers an unfunded linear pension system when workers make labor decisions more often than once in their life. To capture this feature, a three-period-overlapping-generations model is employed. On the one hand, the paper analyzes whether or not a Pay-as-you-go pension scheme is intergenerational Pareto efficient when labor is elastically supplied by the young and the middle-aged people. On the other hand, the focus is on the interregional efficiency of a Pay-as-you-go system when young and middle-aged workers are mobile.
Keywords: H55; J26; J61; 330; pay-as-you-go pension system; overlapping-generations model; intergenerational fairness; labor mobility